Common motifs in ETAA1 and TOPBP1 required for ATR kinase activation - Thada, Vaughn (J Biol Chem, 2019)
DNA damage response Ser/Thr kinases, including ataxia telangiectasia-mutated (ATM) and Rad3-related (ATR), control cell cycle progression, DNA repair, and apoptosis. ATR is activated by ETAA1 activator of ATR kinase (ETAA1) or DNA topoisomerase II binding protein 1 (TOPBP1). Both ETAA1 and TOPBP1 contain experimentally defined ATR activation domains (AADs) that are mostly unstructured and have minimal sequence similarity. A tryptophan residue in both AADs is required for ATR activation, but the other features of these domains and the mechanism by which they activate ATR are unknown. In this study, using bioinformatic analyses, kinase assays, co-immunoprecipitation, and immunofluorescence measures of signaling, we more specifically defined the TOPBP1 and ETAA1 AADs and identified additional features of the AADs needed for ATR activation. We found that both ETAA1 and TOPBP1 contain a predicted coiled-coil motif that is required for ATR activation in vitro and in cells. Mutation of the predicted coiled coils does not alter AAD oligomerization but does impair binding of the AADs to ATR. These results suggest that TOPBP1 and ETAA1 activate ATR using similar motifs and mechanisms.